Transmission lines, quantum graphs and fluctuations on complex networks - Ahmed, Mubarack (2021)
High-frequency devices are commonplace and at their foundations often lie cable networks forming fundamental sub-systems with the primary role of transferring energy and information. With increasing demand for ”more electric” systems, the emerging trends in Internet of Things (IoT), as well as the surge in global mobile data traffic, the complexities of the underlying networks become more challenging to model deterministically. In such scenarios, statistical approaches are best suited because it becomes daunting to accurately model details of such networks.